Optical Isomers of Atorvastatin, Rosuvastatin and Fluvastatin Enantiospecifically Activate Pregnane X Receptor PXR and Induce CYP2A6, CYP2B6 and CYP3A4 in Human Hepatocytes - Korhonova, Martina; Doricakova, Aneta; Dvorak, Zdenek (PloS one, 2015)
Atorvastatin, fluvastatin and rosuvastatin are drugs used for treatment of hypercholesterolemia. They cause numerous drug-drug interactions by inhibiting and inducing drug-metabolizing cytochromes P450. These three statins exist in four optical forms, but they are currently used as enantiopure drugs, i.e., only one single enantiomer. There are numerous evidences that efficacy, adverse effects and toxicity of drugs may be enantiospecific. Therefore, we investigated the effects of optical isomers of atorvastatin, fluvastatin and rosuvastatin on the expression of drug-metabolizing P450s in primary human hepatocytes, using western blots and RT-PCR for measurement of proteins and mRNAs, respectively. The activity of P450 transcriptional regulators, including pregnane X receptor (PXR), aryl hydrocarbon receptor (AhR) and glucocorticoid receptor (GR), was assessed by gene reporter assays and EMSA. Transcriptional activity of AhR was not influenced by any statin tested. Basal transcriptional activity of GR was not affected by tested statins, but dexamethasone-inducible activity of GR was dose-dependently and enantioselectively inhibited by fluvastatin. Basal and ligand-inducible transcriptional activity of PXR was dose-dependently influenced by all tested statins, and the potency and efficacy between individual optical isomers varied depending on statin and optical isomer. The expression of CYP1A1 and CYP1A2 in human hepatocytes was not influenced by tested statins. All statins induced CYP2A6, CYP2B6 and CYP3A4, and the effects on CYP2C9 were rather modulatory. The effects varied between statins and enantiomers and induction potency decreased in order: atorvastatin (RR>RS = SR>SS) > fluvastatin (SR>RS = SS>RR) >> rosuvastatin (only RS active). The data presented here might be of toxicological and clinical importance.
Keywords: Pregnane X Receptor; indoly; stereoizomerie; Humans; cytochrom P450 CYP2B6; cytochrom P450 CYP2A6; rosuvastatin kalcium; kyseliny mastné mononenasycené; Indoles; lidé středního věku; induktory cytochromu P450 CYP2B6; Female; Aged; cytochrom P-450 CYP3A; dospělí; fluvastatin; Cytochrome P-450 CYP2B6; pregnanový X receptor; Fluvastatin; senioři; lidé; Stereoisomerism; Rosuvastatin Calcium; induktory cytochromu P450 CYP3A; Cytochrome P-450 CYP2B6 Inducers; Adult; Cytochrome P-450 CYP3A Inducers; enzymová indukce; Receptors, Steroid; ženské pohlaví; Atorvastatin; Male; Middle Aged; steroidní receptory; nádorové buněčné linie; Cytochrome P-450 CYP2A6; Cytochrome P-450 CYP3A; Hepatocytes; Cell Line, Tumor; mužské pohlaví; Fatty Acids, Monounsaturated; hepatocyty; Enzyme Induction; atorvastatin